RELAXAMENTO PSICOFÍSICO EM CRIANÇAS - Fernandes, Elaine Ferrão (2005)
Research of bibliographical and monographical nature, this paper investigates the psychophysics relaxation in the health area, of children in a period of eight years, between January 1997 and November 2004. Initially, based in neuropsychological literature, it describes the relaxation role in homeostasis and the conscious body health, emphasizing the pleasure and painful behavior. Next, it describes and analyses several relaxation techniques, Jacobson Progressive Relaxation, Schulz Autogenos and Michaux Relaxation. To develop this research it was used 27 databases, due to the lack of production of this theme, per base. As result, it shows the total of 500 articles about relaxation, 200 of them related to children. They are national and international articles, most of them in English. Following this, it classifies these group in production by year, showing a significant increasing, although it is not systematic in number, from 14 articles in 1997 to 39 in 2004. As for the thematic, the data reveals first, the interest in pain, second in breathing problems and third in anxiety. The articles about pain, as they are in more quantity, have more detailed analysis, with discrimination by year, situation type, relaxation usage and pathology characterized by painful behavior. Finally, it is made a classification of the articles due to the usage of relaxation in clinical problems mainly the physical ones, those of affectionate-emotional psychic background, those with no usage of drugs and those with psychic background with the aid of drugs and psychiatric treatment. To discuss the results, several articles researched are also mentioned. Due to the richness of data, showing up the increasing of professionals in this health area, it is suggested further reading.